Sensitivities of Hydrological Processes to Climate Changes in a Central Asian Glacierized Basin - He, Zhihua (Frontiers in Water, 2021)
This study used a glacio-hydrological model to simulate runoff generation processes and glacier evolution in the Ala-Archa basin in Central Asia. Model parameters were calibrated by observations of streamflow, satellite snow cover area (SCA) and annual glacier mass balance (GMB). Temperature and precipitation change scenarios were set up by perturbations of the reference measurements in a 20-year period of 1997 to 2016. Seven temperature warming scenarios with an increment of +1 ℃ and six precipitation change scenarios ranging from 70% to 130% of the reference precipitation were used to investigate the sensitivities of hydrological processes to climate changes in the study basin. Results indicate that: (1) Annual runoff increased with rising temperature (T) and precipitation (P) at rates of 76 mm/+1 ℃ and 62 mm/+10%P, respectively. Glacier area was more sensitive to T changes than to P changes. The total glacier area in the basin decreased with T warming at a rate of -0.47 km2/+1 ℃, whilst increasing with rising P at a rate of 0.16 km2/+10%P. (2) The basin runoff switched from rainfall and groundwater-dominated to ice melt-dominated with warming T, while the dominance of rainfall and groundwater were strongly enhanced by rising P. Proportion of rainfall in the total water input for runoff generation decreased with T warming at a rate of -0.5%/+1 ℃, while increasing with P increases at a rate of 1.2%/+10% P. Ice melt proportion changed with T and P increases at rates of 4.2%/+1 ℃ and -1.8%/+10% P, respectively. Groundwater contribution to total runoff decreased by -2.8% per T warming of 1 ℃, but increased by 1.5% per P increase of 10%. (3) The maximum P changes (±30%) could only compensate the effects of T warming of 0.5 ℃ to 2.5 ℃. Decrease of glacier area caused by 1 ℃ warming cannot be compensated by the maximum P increase of +30%. Increase of annual runoff forced by T warming lower than 2.2 ℃ could be compensated by decrease caused by the maximum P decrease of -30%. The results inform understandings of the hydrological responses to potential climate changes in glacierized basins in Central Asia.